This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Did it with the help of PEMDAS (solving inside the parenthesis first, then doing the exponent before multiplying)
(1 + 2 + 3 + 4)^1 + 4(1 + 2 + 3)^2 + 6(1 + 2)^3 + 4( 1)^4 =
(1 + 2 + 3 + 4)^1 = 10^1 = 10
4(1 + 2 + 3)^2 = 4(6)^2 = 4(36) = 144
6(1 + 2)^3 = 6(3)^3 = 6(27) = 162
4( 1)^4 = 4(1) = 4
10 + 144 + 162 + 4 = 154 + 162 + 4 = 316 + 4 = 320
The answer is 320.